High capacity surface route discharge at the potassium-O2 electrode - Chen, Yuhui; Jovanov, Zarko P.; Gao, Xiangwen; Liu, Jingyuan; Holc, Conrad; Johnson, Lee R.; Bruce, Peter G. (Elsevier, 2018)
Discharge by a surface route at the cathode of an aprotic metal-O2 battery typically results in surface passivation by the non-conducting oxide product. This leads to low capacity and early cell death. Here we investigate the cathode discharge reaction in the potassium-O2 battery and demonstrate that discharge by a surface route is not limited to growth of thin (<10 nm) metal oxide layers. Electrochemical analysis and in situ Raman confirmed that the product of the cathode reaction is a combination of KO2 and K2O2, depending on the applied potential. Use of the low donor number solvent, acetonitrile, allows us to directly probe the surface route. Rotating ring-disk electrode, electrochemical quartz crystal microbalance and scanning electron microscope characterisations clearly demonstrate the formation of a thick > 1 μm product layer, far in excess of that possible in the related lithium-O2 battery. These results demonstrate a high-capacity surface route in a metal-O2 battery for the first time and the insights revealed here have significant implications for the design of the K-O2 battery.